THE USE OF VISUAL VIDEO AS MEDIA TO IMRPOVE STUDENTS ABILITY IN WRITING PROCEDURE TEXT AT THE ELEVENTH GRADE OF SMK NEGERI 1 TOMA - Lies Dian M. Ndraha (Institut Pendidikan Tapanuli Selatan, 2020)
This research aimed at improving students’ ability in writing procedure text through the used visual video as media of teaching. This research was a kind of classroom action research. This research was conducted in two cycles and each cycle consisted of two meetings. The subject of the research was eleventh grade of SMK Negeri 1 Toma which consisted of 12 students. The instruments of data collection were observation paper as the source qualitative data and test as the source of data quantitative in this research. The data were analyzed by using the description method and rubric of writing assessment. The result of data analysis showed that by using visual video as media improved the students’ ability in writing skill, stimulated the students to be more active, got interest, and motivation in joining the class. The result of students’ score in cycle I who passed was only 5 students or 42% while the students who failed was 7 or 58% with the average score was 67. Therefore, the cycle I was unsuccessful so the researcher continued in cycle II. In the cycle II, the students who passed was 10 or 83% while the students who failed was only 2 or 17% with the average score was 77. Based on the result, it can be concluded that the students’ ability in writing got improving, where the MCC is 70. Result of observation paper also got improvement from the students. The activities in the cycle I still got weakness which faced by the students, because of the media is new one for them its looks unfamiliar and there are some activities which undone by researcher, however, the result of observation paper show the improvement by students each meeting. The activities Cycle II was satisfied the students more active and interest in study English for each meeting they feels enjoyable and relax each meeting. Based on the research finding, it is concluded that by using visual video as media to teach writing subject was increasing the students’ ability in writing skill. Therefore, the finding of this research are recommended the English teacher to using visual video to teach English subject